Education of the body in motion (Revista Contexto & Educação, 2024)
This article aims to present a synthesis of thinking about the education of the body from the perspective of a group of intellectuals who discuss this issue, especially through the human sciences, and explore the web of interdependencies configured in the teaching of school physical education. As a research problem, it was analyzed what they think, what are the theoretical references and arguments presented in relation to the “education of the body in movement”. The method of analysis was based on bibliographic research and on the approach of historical understanding of the social phenomenon, according to the configurational theory. It was found that the plurality of interpretations is a conceptual reaffirmation of the academy, of scientific argumentative disputes in establishing the body/child/young school in its fullness. It concludes in defense of acting and intervening inter and transdisciplinary, resignifying initial and continuing education and, concomitantly, pedagogical intervention with regard to the teaching of school physical education and education of the body in movement.
Keywords: Body; Movement; School Physical Education